Albania : 2008 Article IV Consultation, Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Review Under Extended Arrangement, Financing Assurances Review, and Request for Modification of Performance Criteria; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Albania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that over the last decade, Albania's macroeconomic performance has generally been strong and per capita GDP in U.S. dollar terms more than doubled. Strong fiscal policy, largely based on major improvements in tax administration, lowered public debt from 66 percent of GDP in 2001 to 53 percent in 2007. Risks to domestic and external stability have receded somewhat. Domestic credit growth, though still elevated, has decelerated from past highs. The authorities have adapted regulatory and supervisory regimes to keep abreast with the rapidly developing financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet